1994
DOI: 10.1021/bi00186a024
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glycosylation in the Biosynthesis and Activity of Rabbit Testicular Angiotensin-Converting Enzyme

Abstract: Angiotensin-converting enzyme (ACE) is a type I glycoprotein anchored in the plasma membrane by a hydrophobic domain near its carboxyl terminus. The enzymatically active extracellular domain of ACE is slowly released from the cell by cleavage-removal of its membrane-anchoring carboxyl-terminal region. In the present study, we investigated the role of N- and O-glycosylation in intracellular transport and extracellular cleavage-secretion of rabbit testicular ACE. For ACE expression, we used an in vitro translati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 34 publications
1
30
0
Order By: Relevance
“…The molecular mass found for the ACE forms S-1/SP-1/ Sen-1 (80 kDa), S-2/SP-2/Sen-2 (65 kDa) from urine of SHR, SHR-SP, SRHen rats; C-2 (65 kDa) from urine of 1K1C rats; DC-2/D2 (65 kDa) from urine of DOCA salt control and D-2 DOCA salt and BN-2 (65 kDa) from urine of BN rats was much lower than testicular ACE (90 to 100 kDa), which is heavily glycosylated, although they were similar to that of the nonglycosylated form of the single-domain tACE (76 to 84 kDa) 36,37 and the N-domain ACE (65 to 68 kDa) found recently in human urine 19 and ileal fluid. 38 When we compared the forms from WKY rats and ACE BN-1, with 190 kDa and BN-2, with 65 kDa, the data indicated that different strains presented the same enzyme forms.…”
Section: Discussionmentioning
confidence: 96%
“…The molecular mass found for the ACE forms S-1/SP-1/ Sen-1 (80 kDa), S-2/SP-2/Sen-2 (65 kDa) from urine of SHR, SHR-SP, SRHen rats; C-2 (65 kDa) from urine of 1K1C rats; DC-2/D2 (65 kDa) from urine of DOCA salt control and D-2 DOCA salt and BN-2 (65 kDa) from urine of BN rats was much lower than testicular ACE (90 to 100 kDa), which is heavily glycosylated, although they were similar to that of the nonglycosylated form of the single-domain tACE (76 to 84 kDa) 36,37 and the N-domain ACE (65 to 68 kDa) found recently in human urine 19 and ileal fluid. 38 When we compared the forms from WKY rats and ACE BN-1, with 190 kDa and BN-2, with 65 kDa, the data indicated that different strains presented the same enzyme forms.…”
Section: Discussionmentioning
confidence: 96%
“…DISCUSSION Glycosylation is an essential feature of the biosynthesis of ACE. Rabbit tACE, transiently expressed in human HeLa cells in the presence of tunicamycin, a chemical inhibitor of N-linked glycosylation, appeared only in the cytosol and was degraded rapidly (4). Studies of partial glycosylation of tACE by mutation of potential N-linked glycosylation sites indicated that the oligosaccharide chains at each site make different contributions to in vivo stability and localization (6).…”
Section: Identification Of N-linked Glycosylation Sites In Purified Hmentioning
confidence: 99%
“…Expression of ACE in human HeLa cells in the presence of tunicamycin resulted in complete inhibition of glycosylation, rapidly degraded intracellular ACE, and no enzyme released in the medium (4). An enzymatically active ACE was produced with partial glycosylation in a mutant Chinese hamster ovary (CHO) cell line (ldlD), although it was released to a lesser extent (4). Similarly, it was reported (5) that inhibitors of glucosidases I and II in the endoplasmic reticulum (ER) and mannosidase I in the cis-Golgi reduced the amount of oligosaccharide attached to human intestinal ACE and delayed protein release significantly.…”
mentioning
confidence: 99%
See 2 more Smart Citations